New and old puzzles in the morphological conditioning of coronal stop deletion. (July 2021) - MacKenzie, Laurel; Tamminga, Meredith
Abstract: This paper probes the well-documented morphological effect on coronal stop deletion (CSD, also called /t, d/-deletion), by which there is more deletion in monomorphemes like mist than in regular past tense forms like missed . We observe that there are, in principle, additional morphological distinctions that could be made within each category: for instance, the "regular past" category contains perfect and passive participles; the "monomorpheme" category typically contains compounds and suffixed forms. We demonstrate that several of these newly introduced distinctions actually have significant effects on CSD rates in a corpus of Philadelphia English. And we argue that these new distinctions are worth attending to because they have consequences for two existing accounts of the basic morphological effect. In each case, we show that the existing accounts do not straightforwardly capture the additional significant distinctions we identify, calling the explanatory power of those accounts into question.